Pickering emulsion template method induced highly oriented functionalized graphene oxide in PDMS composites to achieve high gas barrier properties. (19th November 2021) - Zhang, Rui; Xu, Zongchao; Zheng, Long; Liu, Li; Wen, Shipeng; Zhang, Liqun
Abstract: Constructing oriented layered filler networks in methyl vinyl silicone rubber (PDMS) composites is an effective strategy to enhance their gas barrier properties. Herein, GO was first functionalized by sodium dodecyl benzene sulfonate (SDBS) and cetyltrimethylammonium bromide (CTAB) to form amphiphilic GO (SCGO). Furthermore, SCGO and PDMS were mixed to form the water-in-oil type SCGO/PDMS Pickering emulsions. A porous PDMS masterbatch contained hollow SCGO shells was further obtained through freeze-drying the SCGO/PDMS Pickering emulsions. Followed by hot pressing, these hollow shells composed of SCGO sheets collapsed to form the oriented filler networks in the PDMS composites. When the content of SCGO was 3 phr, the gas barrier properties of SCGO/PDMS composites increased 85.7% relative to the pure PDMS. Meanwhile, the gas barrier properties of the SCGO/PDMS composites with oriented filler networks were 20–30% higher than those of the SCGO/PDMS composites with random filler networks at the same filler content. Graphical abstract: Image 1 Highlights: Amphiphilic SCGO was designed to prepare water-in-oil SCGO/PDMS Pickering emulsions. Highly oriented SCGO filler networks were constructed in PDMS composites. The oriented SCGO imparted high gas barrier properties to PDMS composites. A novel strategy was developed to achieve highly oriented filler networks.